CUSTOMARY SPEECH IN THE TEING HANG EMPO CEREMONY OF COMMUNITY IN COMPANG WUNIS VILLAGE - Yuliana, Celmi; Kanisius, Rambut; Kara, Yuliana M D K (Lantern: Journal of Language and Literature, 2025)
This study aims to examine the form, meaning and function of indigenous languages in the Teing Hang Empo ceremony which was carried out in Compang Wunis Village, East Manggarai regency, East Nusa Tenggara province. In particular, this research focuses on the language expressed used in this traditional ceremony, namely kepok and torok. In analyzing the form, meaning and function of the two ritual expressions mentioned above, the author uses a qualitative method by referring to the theory of form, the meaning of the language of ritual Palmer 1996; Sharifian 2017 and the function of Language by Hudson, 1986. The results of data analysis show two forms of customary language or ritual language, namely the form of parallelism and the form of metaphor. Similarly, from the meaning of ritual language there are three meanings, namely collective meaning, hope for success and religious meaning. The function of ritual language has three functions, namely the poetic function, the conative function and the emotive function or expressive function.